Prevalence of Foot Pain Across an International Consortium of Population‐Based Cohorts. Issue 5 (25th April 2019) - Gates, Lucy S.; Arden, Nigel K.; Hannan, Marian T.; Roddy, Edward; Gill, Tiffany K.; Hill, Catherine L.; Dufour, Alyssa B.; Rathod‐Mistry, Trishna; Thomas, Martin J.; Menz, Hylton B.; Bowen, Catherine J.; Golightly, Yvonne M.
Abstract : Objective: Despite the potential burden of foot pain, some of the most fundamental epidemiologic questions surrounding the foot remain poorly explored. The prevalence of foot pain has proven to be difficult to compare across existing studies due to variations in case definitions. The objective of this study was to investigate the prevalence of foot pain in several international population‐based cohorts using original data and to explore differences in the case definitions used. Methods: Foot pain variables were examined in 5 cohorts: the Chingford 1000 Women Study, the Johnston County Osteoarthritis Project, the Framingham Foot Study, the Clinical Assessment Study of the Foot, and the North West Adelaide Health Study. One question about foot pain was chosen from each cohort based on its similarity to the American College of Rheumatology pain question. Results: The precise definition of foot pain varied between the cohorts. The prevalence of foot pain ranged from 13% to 36% and was lowest in the cohort in which the case definition specific to pain was used, compared to the 4 remaining cohorts in which a definition included components of pain, aching, or stiffness. Foot pain was generally more prevalent in women and obese individuals and generally increased with age, with the prevalence being much lower in younger participants (ages 20–44 years). Conclusion: Foot pain is common and is associated with female sex, older age, and obesity. Estimates of the prevalence of foot pain are likely to be affected by the case definition used. Therefore, in future population studies, the use of consistent measures of data collection must be considered.